Optical microfiber passive components. Issue 3 (10th September 2012) - Ismaeel, Rand; Lee, Timothy; Ding, Ming; Belal, Mohammed; Brambilla, Gilberto
<x xml:space="preserve">Abstract</x> Optical microfiber waveguides with diameters close to the wavelength of light possess an intriguing combination of properties, such a tight modal confinement, tailorable dispersion, and high nonlinearity, which have been utilized in many passive applications. Here, the key fabrication techniques and optical properties of microfibers are introduced, followed by a discussion of the various passive microfiber devices and sensors. Applications exploiting their strong confinement are reviewed, including harmonic generation, supercontinuum sources, gratings, tips for optical trapping and intracellular sensing and subwavelength light sources, as well as devices based on large evanescent fields such as couplers, interferometers, optical manipulators, sensors, and resonators. Furthermore, the properties and practical intricacies of manufacturing various microfiber resonators are evaluated, with a focus on their applications in sensing ranging from temperature monitoring to current, pressure, refractive index and chemicals detection. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>